Early Aggressive Immunotherapy Improves Functional Outcome in Chronic Immune Sensory Polyradiculopathy - Jasmine Shimin Koh; James Wei Min Tung; Genevieve Lynn Yu Tan-Yu; Thirugnanam Umapathi (Case Reports in Neurological Medicine)
Chronic immune sensory polyradiculopathy (CISP) is an uncommon and treatable inflammatory disorder of the proximal sensory nerve roots. Patients typically present with severe sensory ataxia, normal motor examination, unsteady gait, and normal nerve conduction studies (NCS). We describe an elderly man who presented with a two-week history of progressive numbness of both legs and recurrent falls. He had hyporeflexia, normal strength, severe proprioceptive, and vibration sense loss in both lower limbs and was unable to stand or walk because of severe sensory ataxia. The NCS and MR scan of the spine were normal. Tibial somatosensory evoked potentials revealed proximal conduction defect and localized the pathology to the lumbar sensory nerve roots proximal to the dorsal root ganglion. Cerebrospinal fluid showed cytoalbuminergic dissociation suggestive of inflammation. CISP was diagnosed; he was given aggressive immunotherapy consisting sequentially of corticosteroids with mycophenolate mofetil and three cycles of intravenous immunoglobulin after which he regained independent mobility. Unlike previous reports where patients presented months-years after symptom onset and improved after single-line immunotherapy, our patient presented fairly acutely and made dramatic improvement only after aggressive combination therapy. We urge physicians to recognize this uncommon neurologic cause of sensory ataxia where early aggressive treatment is crucial for better functional outcomes.